เนื้อหาการเมืองในหนังสือพิมพ์รายวัน - มัทนา เจริญวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
Investigates different political news contents. Contents relating to individual matters of politicians and those dealt with policy, interpretative and neutral contents, human interest and development news, positive and negative stories of each individual and types of newspapers were compared. Content analysis and case study were the techniques used in the study. 184 issues of four different newspapers, the Matichon, ThaiPost, ThaiRath, DailyNews, were randomly selected. The coverage of government censure debate was the case study explored. Chi-square was the main statistics used to test the hypotheses. The results of each individual newspaper studied showed that there were: - More attacking rather than supporting contents in the news relating to government and members of parliament. - More contents about individual and personalized of politicians than policy. - More interpretative contents than human interest contents. - More negative than positive contents. The study also revealed that quantity newspapers contained more individual-personalized, human interest and positive contents than quality newspapers. The above findings were, by and large, confirmed by the result of the case study. Besides, the case study found that these newspapers put special emphasis on news relating to political strategies and polling. Dramatization of news and tampering news with reporters opinion was widespread in these newspapers.